Hubungan Sikap Dengan Perilaku Ibu Dalam Melakukan Pijat Bayi Secara Mandiri Di PMB Lismayani Lubis Kab. Simalungun Tahun 2023 - Basaria Manurung (Asosiasi Riset Ilmu Kesehatan Indonesia, 2023)
In the midst of this developing society, people in Indonesia still use traditional health services, especially baby massage and birth attendants. Massaging babies from traditional healers has been a tradition passed down from generation to generation. This study aims to determine the relationship between attitudes and maternal behavior in carrying out baby massage independently at PMB Lismayani Lubis District. Simalungun. This type of research is an analytical survey. Then analyze the dynamics of correlation between phenomena or between risk factors and consequence factors, which are phenomena that cause consequences (influence). There is a relationship between attitude and mother's behavior in carrying out baby massage independently at PMB Lismayani Lubis Kab. Simalungun with a p value of 0.021.